2020
DOI: 10.26418/jeltim.v2i1.37317
|View full text |Cite
|
Sign up to set email alerts
|

Written corrective feedback on students’ thesis writing: an analysis of student-supervisory interactions

Abstract: This study examines written corrective feedback (WCF) provided by the lecturers on their supervisee-students' thesis drafts at the English Education Program, Faculty of Education, Jambi University. Following Kumar and Stracke (2007), the analysis focuses on the types and distribution of WCF by Holmes' (2008) three main categories of speech acts: (a) Referential (editorial, organization, content); (b) Directive (suggestion, question, instruction); and (c) Expressive (praise, criticism, opinion). The use of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The students often put the corrections in their memory to become alert in the next writing, which develops and accelerates the students' writing skills and performance. Through WCF, students are aware of their inaccuracies and errors, which increases students' autonomous learning in writing (Adrefiza & Fortunasari, 2020). Students learn a lot from the WCF since it forms a process in which they become accustomed to handling their errors and inaccuracies from the lecturers' feedback.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The students often put the corrections in their memory to become alert in the next writing, which develops and accelerates the students' writing skills and performance. Through WCF, students are aware of their inaccuracies and errors, which increases students' autonomous learning in writing (Adrefiza & Fortunasari, 2020). Students learn a lot from the WCF since it forms a process in which they become accustomed to handling their errors and inaccuracies from the lecturers' feedback.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a growing interest in studying written corrective feedback (WCF) provided by lecturers on students' writing tasks in the last several years (Bitchener, 2008;Bitchener & Knoch, 2009;Kumar & Stracke, 2007;Adrefiza & Fortunasari, 2020). Although its efficacy and effectiveness remain controversial (Truscott, 1996;Bitchener, 2008), studies have suggested that WCF plays a significant role in developing students' self-regulatory learning (Stracke and Kumar, 2010) and significantly accelerates the students' writing skills and performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feedback in writing is described as written comments to a student's written product. It is available in written corrections, remarks, or markings [9,13]. In this study, feedback refers to the supervisor's comments and markings on the flaws and mistakes in the students' research proposals.…”
Section: Definition Of Feedbackmentioning
confidence: 99%